AWARDS IN MEDICINE AND DERMATOLOGY - Aboud, Khalid M.Al; Aboud, Ahmad M. Al; Hawsawi, Khalid A.Al; Ramesh, V (Journal of Ayub Medical College Abbottabad, 2006)
An award is something granted or given in recognition of one's meritorious work. The value of giving prizes to recognize exceptional work, and the need to publicize such awards to enhance their value cannot be disputed. In the field of medicine, there are several international awards. These include, the King Faisal International Prize for Medicine1,2, Nobel Prize3, Prince Mahidol Award 4and Sheikh Hamdan Bin Rashid Al Makhtoum Award for Medical Sciences.5 In addition, there are many other international awards for medicine, including the Gairdner Foundation International awards for outstanding biomedical research and the American Medical Association (AMA) Foundation's international awards in Medicine and Public Health for Outstanding international service. Kuwait foundation for advancement of sciences also gives several medical awards. The most famous one is the Nobel Prize for Physiology or Medicine. It was first given in 1901. The Nobel Prize is widely regarded as the single most prestigious award given for intellectual achievement in the world. The Nobel Prize was established from a fund bequeathed for that purpose by the Swedish inventor and industrialist Alfred Nobel in his will drafted in 1895 for the award of five prizes annually in the fields of Physics, Chemistry, Physiology or Medicine, Literature and Peace. A sixth for Economics was added in 1968. Part of the Nobel Prize's prestige stems from the serious research that goes into the selection of the prizewinners. Prizes may be given only to individuals, except for the Peace Prize, which may be given to an institution. Each Nobel Prize consists of a gold medal, a diploma bearing a citation, and a sum of money, the amount of which depends on the income of the Nobel Foundation. A sum of $1,120,000 accompanied each prize in 1996. A Nobel Prize is given entirely to one person, divided equally between two persons, or shared by three persons. Table-1 shows the previous winners, in the last five years, of Nobel Prize for physiology or medicine.